A Review of Reza Shah-Kazemi's Common Ground Between Islam & Buddhism - Arief Arman (Elkuator Research and Publication, 2025)
At its core, this book offers crucial insights on the similarities between Islam and Buddhism at the transcendental level. The captivating text explores ideas around several relevant and significant themes that fall within three chapters: Setting the Scene, Oneness: The Highest Common Denominator, and Ethics of Detachment and Compassion. Shah-Kazemi expertly weaves through the intricacies of comparing the two distinct faith systems. The assessment is thorough and opens the possibility of looking at both traditions in a different light – the view which expresses a perennial truth that human beings are both simultaneously embedded and transcendent, with the immense potential for spiritual growth. The London-based academic points out that the objective of his work is to be as inclusive as possible, both as regards to ‘the other’ and to the Muslim perspective. Its implication is that the text is not just to reach out to Buddhists as an invitation to consider the Islamic tradition, but to also explain central concepts within Buddhism which might not be too familiar to Muslims.